Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection by Intranasal or Intratesticular Route Induces Testicular Damage. (18th February 2022) - Li, Can; Ye, Zhanhong; Zhang, Anna Jin Xia; Chan, Jasper Fuk Woo; Song, Wenchen; Liu, Feifei; Chen, Yanxia; Kwan, Mike Yat Wah; Lee, Andrew Chak Yiu; Zhao, Yan; Wong, Bosco Ho Yin; Yip, Cyril Chik Yan; et al.
Abstract: Background: The role of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the pathogenesis of testicular damage is uncertain. Methods: We investigated the virological, pathological, and immunological changes in testes of hamsters challenged by wild-type SARS-CoV-2 and its variants with intranasal or direct testicular inoculation using influenza virus A(H1N1)pdm09 as control. Results: Besides self-limiting respiratory tract infection, intranasal SARS-CoV-2 challenge caused acute decrease in sperm count, serum testosterone and inhibin B at 4–7 days after infection; and chronic reduction in testicular size and weight, and serum sex hormone at 42–120 days after infection. Acute histopathological damage with worsening degree of testicular inflammation, hemorrhage, necrosis, degeneration of seminiferous tubules, and disruption of orderly spermatogenesis were seen with increasing virus inoculum. Degeneration and death of Sertoli and Leydig cells were found. Although viral loads and SARS-CoV-2 nucleocapsid protein expression were markedly lower in testicular than in lung tissues, direct intratesticular injection of SARS-CoV-2 demonstrated nucleocapsid expressing interstitial cells and epididymal epithelial cells, While intranasal or intratesticular challenge by A(H1N1)pdm09 control showed no testicular infection or damage. From 7 to 120 days after infection, degeneration and apoptosis of seminiferous tubules, immune complex deposition, and depletion of spermatogenic cell and spermatozoa persisted. Intranasal challenge with Omicron and Delta variants could also induce similar testicular changes. This testicular damage can be prevented by vaccination. Conclusions: SARS-CoV-2 can cause acute testicular damage with subsequent chronic asymmetric testicular atrophy and associated hormonal changes despite a self-limiting pneumonia in hamsters. Awareness of possible hypogonadism and subfertility is important in managing convalescent coronavirus disease 2019 in men. Abstract : Severe acute respiratory syndrome coronavirus 2 intranasal infection causes testicular damage and associated hormonal changes despite a self-limiting pneumonia in hamsters. Awareness of possible hypogonadism and subfertility is important in managing convalescent coronavirus disease 2019 in males.